Vector mechanics for engineers: statics and dynamics - Beer, Ferdinand P...[et al] (Tata McGraw-Hill, 2006)
Vector mechanics for engineers: statics and dynamics / Beer, Ferdinand P...[et al]. -- New Delhi: Tata McGraw-Hill, 2006 531.112 V396e7 7th ed No. of Copies : 1